Tariffs, Unemployment, and the Current Account: An Intertemporal Equilibrium Model - Shouyong Shi (Queen's University, Department of Economics, 1997)
This paper integrates labor market search into an intertemporal equilibrium model to analyze the dynamic macroeconomic effects of a tariff. The model captures the intuitive argument in the earlier literature that a permanent increase in the tariff improves the country's terms of trade, which tends to reduce the product wage and stimulates labor demand. However, the tariff also increases the price of the consumption goods bundle and reduces the marginal utility of wealth measured by imports. This consumption bundle effect raises the reservation wage and the product wage. When the consumption smoothing motive is realistically strong, the consumption bundle effect dominates the product wage effect and so tariffs reduce employment in both the short run and the long run.
Keywords: F40; J64; F30; 330; Tariffs; Unemployment; Search; Vacancy; Terms of trade